The Impact of Physical Activity in Elderly - Adinda Nadira Larasati; Elman Boy (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2019)
Physical activity has been identified as a protective factor for non-communicable diseases such as cardiovascular disease, stroke, diabetes, some types of cancer and has been linked to slowing the onset of dementia, improved mental health, and improved quality of life and well-being. The increase in the number of the elderly population causes the need for special attention to the elderly, so that in addition to having a long life, the elderly can also enjoy their old age happily. Special attention is needed on promotional measures to support the elderly to participate in physical activity to help overcome the decline in functional capacity associated with aging. This literature review aims to provide an understanding of the impact of physical activity on the elderly. Elderly who do physical activity will get many positive effects, ranging from increasing bone density, reducing fat accumulation, increasing body mass index, reducing the risk of damage to the musculoskeletal system, reducing the risk for the development of cardiovascular disease, cancer, other chronic diseases, as hypertension management because it can lower blood pressure. Physical activity also greatly affects the increase in dopamine levels and changes in neutrophic factors that have neuroprotective functions so that they can inhibit cognitive decline and dementia, and BDNF as a neutrophic factor can help the elderly prevent symptoms of depression or anxiety.